2017
DOI: 10.1149/2.0261801jss
|View full text |Cite
|
Sign up to set email alerts
|

Broadband, White Light Emission from Doped and Undoped Insulators

Abstract: We present data on broadband, white light emission from insulating hosts under intense excitation in the near infrared in host materials that are undoped, partially-doped with rare earth ions, and that contain stoichiometric concentrations of rare earth ions. Much of the emission is found to have a blackbody-like structure in the visible and near infrared region. The origin of the emission as from a blackbody is also supported by the temporal characteristics of the emission in response to turning on and off th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…500 °C), and saturation of the WLE intensity for higher excitation powers), thus several different theories have already been proposed for interpretation of the WLE phenomenon. Those propositions include cooperative emission, up-conversion emission following multiphoton absorption, thermal radiation, , photon avalanche, supercontinuum generation, or intervalence charge transfer (IVCT). , The latter deserves closer attention, as formation of mixed valence pairs, i.e., Yb 3+ and Yb 2+ , may not be ignored during intense pumping with the 975 nm CW laser in a vacuum. In such a case, the charge transfer process may occur either by optical or thermal excitation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…500 °C), and saturation of the WLE intensity for higher excitation powers), thus several different theories have already been proposed for interpretation of the WLE phenomenon. Those propositions include cooperative emission, up-conversion emission following multiphoton absorption, thermal radiation, , photon avalanche, supercontinuum generation, or intervalence charge transfer (IVCT). , The latter deserves closer attention, as formation of mixed valence pairs, i.e., Yb 3+ and Yb 2+ , may not be ignored during intense pumping with the 975 nm CW laser in a vacuum. In such a case, the charge transfer process may occur either by optical or thermal excitation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The WLE phenomenon of insulating nanophosphors was first observed and described by Wang and Tanner in 2010, who had studied an odd broadband emission from Yb 2 O 3 , Sm 2 O 3 , and CeO 2 powders that occurred under intense 975 nm laser excitation . Due to its untypical character, the WLE was first seen as a new type of cold emission and further investigated by a number of researchers, showing its anti-Stokes character that was in many ways quite similar for a broad range of various materials, including graphene, metals, or oxides. The WLE reveals a number of uncommon properties, i.e., (i) broad-band emission, (ii) independence on the excitation wavelength, (iii) threshold behavior of light emission, (iv) sensitivity to the vacuum level, (v) moderate average temperature (lower than ca. 500 °C) of the emitting sample, or (vi) multiphoton character.…”
Section: Introductionmentioning
confidence: 99%
“…A vivid example is the appearance of broadband "white" emission (BBWE) in nanoscale dielectric materials when they are excited by intense laser radiation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In most cases, this emission was observed in compounds doped with rare-earth (RE) ions upon excitation into the absorption band of these ions. An analysis of these publications indicates that there are different points of view on the nature of the observed phenomenon and the processes responsible for it.…”
Section: Introductionmentioning
confidence: 99%
“…The rst group of researchers believes that the observed emission is inherently thermal (blackbody). 1,5,[11][12][13][14] According to the second group of opinions, it represents luminescence and is not associated with sample heating. 2,3 For example, the authors of 1,5 attribute the thermal nature to the BBWE observed when the nanosized particles of Y 2 O 3 :Yb,Er are excited into the absorption band of Yb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, S. Tabanli et al. have reported the white light emission from the Yb 2 O 3 at 1 atm and at 0.03 mbar pressure . However, the heat associated/incandescent‐like white light of continuum spectrum and IOB produced by host sensitized Yb 2 O 3 :Er 3+ phosphor under 980 nm CW laser diode excitation has not been reported till date.…”
Section: Introductionmentioning
confidence: 99%